Profil uretritis gonokokus dan non-gonokokus di Poliklinik Kulit dan Kelamin RSUP Prof. Dr. R. D. Kandou Manado periode Januari â€“ Desember 2012 - Sambonu, Alson .; Niode, Nurdjannah J.; Pandeleke, Herry E.J. (e-CliniC, 2016)
Abstract: Gonococcal urethritis (GU) is a sexually transmitted infection (STI) which is caused by Neisseria Gonorrhoeae bacteria. In GU, there is an urethral inflammation caused by negative Gram diplococcus ( its natural reservoir is human) and the symptoms are purulent discharge from external urethral orificium, burning sensation during urination, distal urethra itching, dysuria, vaginal or penile discharge, and erection pain. Non-Gonococcal Urethritis (NGU) is an urethral inflammation that is not caused by Gonococcal infection, but due to Chlamydia trachomatis and Ureaplasma urealyticum. The symptoms are penile discharge, burning sensation and pain during urination, and itching. This study aimed to obtain the profiles of gonococcal and non-gonococcal urethritis in Dermatovenereology Clinic of Prof. Dr. R. D. Kandou General Hospital Manado from January to December 2012. This was a retrospective descriptive study based on GU and NGU types, symptoms, sexual partner, occupation, and farmacological therapy. The results showed that of 74 STI cases there were 11 GU cases (14.9%) and 4 UNG cases (5.4%). Most of GU and NGU patients were 25-44 years (n = 10, 66.7%), with dysuria (n = 11, 73.3%), prostitute as sexual partner (n = 10, 66.7%), working as entrepreneur (n = 12, 80%), and farmacological therapy for GU is cefixime (n = 9, 81.8%) and for NGU is doxycyclin (n = 3, 75%). Keywords: gonococcal urethritis, non-gonococcal urethritisÂ Abstrak: Uretritis gonore (UG) merupakan suatu penyakit infeksi menular seksual (IMS) yang disebabkan oleh kuman Neisseria gonorrhoeae. Pada UG terjadi peradangan uretra oleh diplokokus Gram negatif yang reservoir alaminya ialah manusia dan ditandai adanya pus yang keluar dari orifisium uretra eksternum, rasa panas, gatal di bagian distal uretra, disuria, polakisuria, keluar duh tubuh dari ujung uretra yang kadang-kadang disertai darah dalam urin, dan disertai rasa nyeri saat ereksi. Uretritis non Gonore (UNG) adalah suatu peradangan pada uretra yang bukan disebabkan oleh infeksi gonokokus seperti Chlamydia trachomatis dan Ureaplasma urealyticum dengan gejala seperti discharge dari penis, rasa terbakar atau sakit saat buang air kecil dan gatal. Penelitian ini bertujuan untuk mengetahui profil uretritis gonokokus dan non gonokokus di Poliklinik Kulit dan Kelamin RSUP Prof. Dr. R. D. Kandou Manado periode Januari-Desember 2012. Jenis penelitian ini deskriptif retrospektif berdasarkan jenis penyakit UG dan UNG, umur, keluhan, pasangan seksual, pekerjaan, dan terapi farmakologis. Hasil penelitian menunjukkan dari 74 kasus IMS terdapat 11 kasus UG (14,9%) dan 4 kasus UNG (5,4%). Penderita UG dan UNG terbanyak pada kelompok umur 25-44 tahun (n = 10, 66,7%), dengan keluhan disuria (n = 11, 73,3%), pasangan seksual dengan WPS (n = 10, 66,7%), pekerjaan wiraswata (n = 12, 80%), serta terapi farmakalogis pada UG ialah cefixime (n = 9, 81,8%) dan pada UNG ialah doxycyclin (n = 3, 75%).Kata kunci: uretritis gonokokus, uretritis non gonokokus